Handel, zaopatrzenie oraz rzemiosło i usługi w Zielonej Górze w latach 80. XX wieku = Trade, supplies, crafts and services in Zielona Góra in the 1980s - Domke, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article raises the subject of the supply of trade, crafts and services at the terrain of the city of Zielona Gora in the last decade of the Polish People?s Republic. It describes the infrastructure of the establishments and outlets a well as the assortment that they offered. The location and the supply of the butcher?s stores, bakeries, general goods stores, "Ruch" kiosks, toy stores and the city?s marketplace were characterized.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia